"The Gypsy Baron" Operetta (1885) as a musical document of a certain age = Operetka "Baron cygański" (1885) jako muzyczny dokument pewnej epoki - Piotrowska, Anna G. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Considered a musical monument to the Austro-Hungarian Empire "The Gypsy Baron" (originally "Der Zigeunerbaron") of 1885 composed by Johann Strauss II (1825-1899) reveals how important position Maria eresia had in the Empire in the long nineteenth century. It is also a great example of keeping, in Vienna at the end of the nineteenth century, hold of the memory of her politics.
Keywords: Maria Teresa Walburga Amalia Christina von Habsburg (1717-1780); "The Gypsy Baron"; "Der Zigeunerbaron"; operetta; operetka; Gypsies in music; Strauss, Johann (syn) (kompozytor austriacki; 1825-1899); "Baron cygański"